Analiza rezultatov preizkusa hoje na dva kilometra zaposlenih v Zdravstvenem domu Murska Sobota - Horvat, Martina (Zdravstveno varstvo, 2002)
Connection between body mass index and physical fitness index of the employed in Murska Sobota health centre has been established by the help of a 2 km walkexperiment. Participants were divided into groups regarding their gender, age and profession. Alltogether, 118 participants were included in this experiment. It has been established that men have higher body mass index, which increases with age. The highest body mass index is among physicians. Regarding the physical fitness index, it has been established that it does notchange with age. The most important finding is, that participants with acceptable body weight (ideal body mass index) have the highest aerobic capacity, i. e. physical fitness index.
Keywords: Body mass index; gibanje; Health behavior; Health manpower; Hoditi; hoja; Physical endurance; Telesna masa, indeks; Telesna vzdržljivost; telesne sposobnosti; Walking; Zdrav način življenja; zdravo življenje; Zdravstveni delavci